Development and initial validation of a postal survey evaluation of community pharmacists' opinion regarding falsified (counterfeit) medicines in Hampshire (UK) - Ravina Barrett; Hussein A. Al-Mousawi (GarVal Editorial Ltda., 2018)
Context: Falsified-medicines pose a worldwide problem to patients, healthcare professionals, pharmaceutical companies, and governments. Community pharmacists are usually the last points of contact with patients and can protect them by quarantining falsified medicines. Hence, their opinions are valuable in exploring how the profession can combat this. Aims: To explore the opinion of pharmacists with respect to falsified medicines. Methods: A postal survey was developed and distributed to 359 pharmacies via the local pharmaceutical committee in Hampshire, UK. Descriptive statistics and hypothesis testing was conducted. Hypothesis testing (95% CI, α = 0.05) will be conducted to identify any gender differences, differences based on years of experience and differences based on number of working hours per week. Results: A 14% response rate was achieved. Pharmacists surveyed believe that falsified-medicines pose a significant problem to the profession on a five-point Likert scale (4.02 ± 1.078). A pharmacist's intervention can prevent or disrupt the supply to patients (4.12 ± 0.824) and training courses can improve pharmacist's knowledge (4.06 ± 0.843). Pharmacists are not confident and capable in identifying falsified-medicines (2.62 ± 1.105). This is surprising and unexpected because pharmacists are medicines-expert. A 10-item scale is validated (72.2% Cronbach alpha). Conclusions: Falsified-medicines pose a small but significant and growing challenge to the profession. There is underutilization of the high street community pharmacist in identifying falsified-medicines. Healthcare professionals should report suspect counterfeits to the MHRA.